THE EFFECTIVENESS OF SOME ECTOMYCORRHIZAL FUNGI IN ALGINATE BEADS IN PROMOTING THE GROWTH OF SEVERAL DIPTEROCARP SEEDLINGS - SUPRIYANTO SUPRIYANTO (BIOTROPIA, 1999)
The effectiveness of six species of ectomycorrhizal fungi (Scleroderma columnare, S.dictyosporum, Laccaria toccata, Rhizopogon luteolus, Amanita umbronata and Descomyces sp.) in alginate beads in promoting the growth of four species of dipterocarp seedlings (Shorea pinanga, S.leprosula, S.ovalis and Hopea odorata) were studied. Different sodium alginate concentrations of 5 g, 10 g, 15 g and 20 g/L were tested to find out the best bead's elasticity and spore germination. Seedling height, Relative Field Mycorrhizal Dependency, percentage of mycorrhizal colonization, nutrient absorption, and the formation of Hartig's net and mantle structure of dipterocarp seedlings were observed 4 months after inoculation. The best elasticity of alginate beads was found in the concentration of sodium alginate of 15 g/L. The best growth increment was found in Hopea odorata inoculated with Amanita umbronata (126.60 %) followed by Shorea pinanga inoculated with Descomyces sp. (27.10%), Shorea ovalis inoculated with Amanita umbronata (26.90 %) and Shorea leprosula inoculated with Descomyces sp. (24.20 %) over the control. The highest Relative Field Mycorrhizal Dependency was found in Hopea odorata followed by Shorea ovalis, S. pinanga and S. leprosula. The highest mycorrhizal colonization was obtained in Shorea pinanga inoculated with Descomyces sp. (75%), while inoculation with Amanita umbronata on S.leprosula, S.ovalis and Hopea odorata increased mycorrhizal colonization i.e. 64.5 %, 52.5%, and 46.2 %, respectively. Hartig's net and mantle structures were well formed in Shorea leprosula as well as S.ovalis seedlings with all mycorrhizal fungi tested, while in S.pinanga seedlings these structures were only well formed with Descomyces sp. There is no clear difference in P levels in the leaves following inoculation as compared to the controls. Key words: Mycorrhizas/AlginateÂ  beads/Scleroderma columnare/Scleroderma dictyosporumlLaccaria laccatalRhizopogon luteoluslAmanita umbronatalDescomycesÂ  sp./Growth/Dipterocarpace-ae/Seedlings.